Goals and Values in Education and Upbringing – Historical Contexts - Kulbaka, Jacek (Ruch Filozoficzny, 2022)
The text contains information on the history of pedagogical thought. The author’s intention was to show universal goals and educational values and ideals throughout history (from antiquity to the present).